BS EN 61753-053-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 053-02. Non-connectorized single-mode fibre, electrically controlled, variable optical attenuator for category C. Controlled environments (28th November 2020) - British Standards Institution
No abstract available